Analisis Perbandingan Gaya Gempa Berdasar SNI 1726 2002 Dan SNI 1726 2012 Terhadap Struktur Atas Gedung Perpustakaan Dan Laboratorium Politeknik Negeri Madiun - Rohman, Rosyid Kholilur (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Indonesia is a country whose territory lies at the confluence of three tectonic plates, so that Indonesia's territory becomes earthquake prone. Indonesia it self has had regulations on earthquake resistance in SNI 1726 2002 but 10 years later a new regulation was issued SNI 1726 2012. To find out the difference it will be compared to the application of SNI 1726 2002 and SNI 1726 2012 to the structure Library and Laboratory Politeknik Negeri Madiun. The results of the analysis obtained the basic shear force of SNI 1726 2002 amounting to 72029,23 kg while the SNI 1726 2012 amounted to 133760,1 kg. The distribution of earthquake forces to each floor of SNI 1726 2012 is 85,7% greater than SNI 1726 2002. The inter-floor deviation of SNI 1726 2012 is greater than SNI 1726 2002. The results of calculation of reinforcement requirements based on SNI 1726 2002 are obtained.